A escritura da presença na crônica televisual de Fernando Gabeira - Chiarioni, Bruno Teixeira (2017)
This research is geared towards Fernando Gabeira’s journalistic narrative. Attentive to unexpected storylines, the subjective tone and the non-assertive nature of such narrative, this research seeks to understand it as an atypical voice in the context of the greater Brazilian press, for it avoids newscasting and its calamitous rhetoric, in light of Roland Barthes’ writings. Such concept is conceived in the field of literary criticism. Knowing that the Barthesian writing is defined in contrast to the myth and its rumor, in this paper we will consider both concepts useful to understand Gabeira’s discourse, especially the televisual one. We work with the hypothesis that, in this case, the journalist reveals the writer, especially since his anchoring in the televisual chronicle is preceded by an oeuvre with seven books, whose style is comparable to the one Gabeira currently dares to adopt on the screen. The state of the art involves comprehensive works on literary journalism, from the New Journalism, internationally led by journalists/writers such as Tom Wolfe, Truman Capote, Gay Talese, John Hersey to the kind of journalism dedicated to journalistic chronicles named the New Latin American Journalism, practiced by exponential names such as Martin Caparrós, Leila Guerriero, among others, and having in Brazil representatives such as Dorrit Harazim and Eliane Brum. The theoretical framework contains Barthes’ works, especially the first one that includes Writing Degree Zero and Mythologies, as well as his best presentations. The research corpus is made up of five editions of the Fernando Gabeira program, from the cable channel Globo News, broadcast between September 2013, when the attraction opened, and the first quarter of 2017, when closing the writing of this thesis. The choice of editions is made especially because this researcher believes that these productions are more closely connected to the propositions raised in this thesis. From the methodological point of view, the research is bibliographic and documental. The relevance of the work is connected to the use of the Barthesian Semiology, which is currently considered crucial for the understanding of the Medias, and also to televisual discourse, rarely targeted by the sophisticated analytical procedures of the author